2008
DOI: 10.1159/000129624
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Responses to Oral Vaccines in Developing Countries

Abstract: Oral vaccines which are intended for global use do not necessarily induce the same immune responses in all children worldwide. In fact, several vaccines often induce less frequent and lower mean antibody responses in children in developing countries, suggesting that the vaccines may be less protective among children in these areas. Though the reasons for this less vigorous response are not completely understood, it appears that nutrition-related factors, including both protein-calorie and micronutrient malnutr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 112 publications
0
20
0
Order By: Relevance
“…Of particular interest would be to assess the adjuvant effect in malnourished children in developing countries who are known to respond less well to oral vaccines [22]. Furthermore, previous studies with the first-generation ETEC vaccine have suggested that lower doses of vaccine might be needed to improve tolerability in younger age groups [8].…”
Section: Discussionmentioning
confidence: 99%
“…Of particular interest would be to assess the adjuvant effect in malnourished children in developing countries who are known to respond less well to oral vaccines [22]. Furthermore, previous studies with the first-generation ETEC vaccine have suggested that lower doses of vaccine might be needed to improve tolerability in younger age groups [8].…”
Section: Discussionmentioning
confidence: 99%
“…6,7 This was of particular importance in view of the fact that other oral vaccines had been found to be less efficacious in developing world settings. 8 Recognizing that the vaccine donation would cover only the first three years of the program, the partners also worked closely to address the long-term sustainability of the vaccine program.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is generally necessary to incorporate a mucosal adjuvant into the vaccine formulation in order to overcome these challenges, although none have been licensed for oral vaccines to date [36]. A consistent trend has been observed where candidate oral vaccines often perform less effectively in subjects during field trials in endemic areas of developing countries when compared to subjects from developed nations [39]. This phenomenon is known as the "Tropical Barrier" and may have several underlying causes [19].…”
Section: Poor Mucosal Immunogenicity (Hypo-responsiveness and Tolerance)mentioning
confidence: 99%